2004
DOI: 10.1159/000077348
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Variables for Cancer-Related Survival in Node-Negative Colorectal Carcinomas

Abstract: Background/Aim: The efficacy of adjuvant treatment in node-negative colorectal carcinoma is unproven. The purpose of this study was to analyze the prognostic value of routinely detectable clinicopathological variables in order to identify subgroups of node-negative colorectal cancer patients at a high risk of a recurrence. Methods: Seventy-three patients who did not receive radio- or chemotherapy were selected among 112 node-negative colorectal cancer patients who underwent curative resection. Follow-up was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…In addition, this study showed that age pathological T, and tumor recurrence were independent prognostic factors in patients with colon cancer. Consistent with our results, previous studies have also demonstrated that advanced age, higher pathological T and tumor recurrence are associated with poor prognosis in patients with colon cancer (31)(32)(33). Notably, this study revealed that the results of the prognostic model were consistent with actual survival prognostic information in different groups based on hierarchical analysis of age, higher pathological T and tumor recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this study showed that age pathological T, and tumor recurrence were independent prognostic factors in patients with colon cancer. Consistent with our results, previous studies have also demonstrated that advanced age, higher pathological T and tumor recurrence are associated with poor prognosis in patients with colon cancer (31)(32)(33). Notably, this study revealed that the results of the prognostic model were consistent with actual survival prognostic information in different groups based on hierarchical analysis of age, higher pathological T and tumor recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…In an analysis of 124 patients with lymph node‐negative colorectal cancer who underwent curative resection, the 5‐year survival rate was 87% for patients with PNI‐negative tumors versus 57% for patients with PNI‐positive tumors ( P < .006) 86. Other studies similarly have indicated that positive PNI status portends a worse outcome in patients with lymph node‐negative colorectal tumors 87‐89. This suggests that PNI indicates a more aggressive tumor phenotype and may be useful in selecting a subgroup of lymph node‐negative patients who could benefit from adjuvant therapy.…”
Section: Clinical Significancementioning
confidence: 99%
“…7 The prognostic significance of PNI is widely advocated in malignancies of the head and neck and prostate, [8][9][10] but controversies exist in colorectal cancer. [11][12][13][14] In T1-2 early rectal cancer, PNI is one of the adverse pathologic features in selecting patients undergoing local excision. But whether it can be used as a criterion to select patients receiving chemoradiotherapy in T3N0 patients is still unknown to us.…”
mentioning
confidence: 99%